2013
DOI: 10.1007/s40145-013-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase relations in perovskite-structured BiFeO3-based multiferroic compounds

Abstract: Abstract:In this review, the state of the art in understanding the structural phase relations in perovskite-structured BiFeO 3 -based polycrystalline solid solutions is presented and discussed. Issues about the close relation between the structural phase and overall physical properties of the reviewed systems are pointed out and discussed. It is shown that, by adjusting the structural symmetric arrangement, the ferroelectric and magnetic properties of BiFeO 3 -based polycrystalline solid solutions can be tuned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…(a) The polar Bi-O network around the octahedral sub-lattice and the concomitant symmetry distortions, which can be enhanced when [TiO 6 ] octahedra are also present, given that Ti 4 þ cations show particularly extensive flexibility in their coordination geometry [29,30]. (b) Microstructure and compositional or chemical disorder can give rise to the stabilization of cluster-type scenarios which facilitate the polarization phenomena [15,23,31].…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…(a) The polar Bi-O network around the octahedral sub-lattice and the concomitant symmetry distortions, which can be enhanced when [TiO 6 ] octahedra are also present, given that Ti 4 þ cations show particularly extensive flexibility in their coordination geometry [29,30]. (b) Microstructure and compositional or chemical disorder can give rise to the stabilization of cluster-type scenarios which facilitate the polarization phenomena [15,23,31].…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…15 Perovskite-type of BiFeO 3 demonstrates the coexistence of multiferroic, ferroelectric and antiferromagnetic properties at room temperature with Neel temperature (TN ~367°C) and Curie temperature (TC ~830°C). 16 It has been reported that synthesis of BiFeO 3 @carbon core/shell nanofibres with different thickness of carbon layers were successful and are stable under visible light irradiation and could be easily recycled, indicating that they can be used as effective photocatalysts under visible light. 17 Hydrothermal synthesis of BiFeO 3 using KOH concentration of 4 M have been done in order to get the pure phase of bismuth ferrite to increase the photodegradation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention has been paid to BiFeO 3 because it considers the only material has stable multiferroic properties at room temperature [2][3][4]. Its ferroelectricity cure temperature is 830 °C and the ferromagnetic Neel's temperature is 370 °C [5][6][7]. BiFeO 3 has been utilized in many applications such as industry of radio, television, microwave and satellite communications, audio-video, digital recording and, as permanent magnets, information storage [8], transducer and magnetoelectric coupling [9,10].…”
Section: Introductionmentioning
confidence: 99%